Strengthening Workforce Sustainability for Community-Based Coffee Tourism Development in Bali - Reza Maulana Putra (Bali Tourism Board, 2026)
Community-based coffee tourism has emerged as an innovative approach to promoting sustainable rural development by integrating agricultural heritage, local culture, and tourism experiences. In Bali, coffee tourism provides significant opportunities to diversify rural livelihoods, preserve traditional farming practices, and strengthen community participation. However, the long-term sustainability of this sector depends largely on the resilience and capacity of its workforce. This study examines the key factors influencing workforce sustainability in community-based coffee tourism development in Bali. Employing a qualitative literature review approach, the study synthesizes recent scholarly publications on coffee tourism, agritourism, community-based tourism, workforce sustainability, human resource development, and tourism governance published between 2020 and 2026. The collected literature was analyzed using thematic analysis to identify three interconnected dimensions of workforce sustainability: competency development and human resource capacity, governance coordination and institutional integration, and community empowerment with inclusive development. The findings indicate that workforce sustainability extends beyond technical skill development and requires integrated governance systems, continuous learning opportunities, stakeholder collaboration, and participatory community engagement. Coffee farmers increasingly perform multifunctional roles as producers, tour guides, entrepreneurs, and cultural interpreters, requiring diverse competencies in hospitality, digital marketing, communication, and sustainable tourism management. Furthermore, effective institutional coordination among government agencies, customary village institutions, educational organizations, cooperatives, and tourism stakeholders is essential for aligning workforce development with destination planning. Community empowerment, gender inclusion, youth participation, and digital transformation further enhance workforce resilience and create diversified livelihood opportunities. This study proposes an integrated workforce sustainability framework that combines human capital development, collaborative governance, and inclusive community participation to strengthen the competitiveness and long-term sustainability of Bali's community-based coffee tourism sector while supporting broader rural development and sustainable tourism objectives.